An impulse oscillometry system is less efficient than spirometry in tracking lung function improvements after intravenous antibiotic therapy in pediatric patients with cystic fibrosis. Issue 11 (4th September 2015) - Buchs, Clélia; Coutier, Laurianne; Vrielynck, Stéphanie; Jubin, Virginie; Mainguy, Catherine; Reix, Philippe
Summary A literature search identified one retrospective study on the responsiveness of impulse oscillometry (IOS) in pediatric patients with cystic fibrosis. The aim of this prospective observational study was to assess this property in an adequately powered study after intravenous antibiotic therapy (IVAT) administered for an acute episode of pulmonary exacerbation. Spirometry and IOS were done on the same day as the start and the end of IVAT. Data from 34 patients' of mean age 11.9 years (range, 5–17 years) were studied. The mean FEV1 at the start and at the end of the IVAT was 73.1 ± 23.8% (range, 23.4–122%) and 88.3 ± 21.3% (range, 29.4–131%), respectively. The mean relative change (mean ± SD) was 20.2 ± 14.2% for FEV1 (ΔFEV1), −21.9 ± 23.8% for reactance at 5 Hz (ΔX5) and –13.4 ± 18.9% for resistance at 5 Hz (Δ R5) (all P‐values <0.05). There was a weak but significant correlation between ΔFEV1 and ΔX5 (r =–0.473; p = 0.01). The magnitude of improvement of ΔX5 was not statistically different between patients with normal versus abnormal lung function at the start of IVAT. Furthermore, using ΔX5 alone as an outcome measure of IVAT efficiency resulted in a significant improvement in 44% of the patients, while it was 79% with ΔFEV1. These results indicate that IOS may track changes after IVAT, but that this improvement may be insufficiently evaluated using IOS alone. Pediatr Pulmonol. 2015; 50:1073–1081. © 2015 Wiley Periodicals, Inc.